2014
DOI: 10.4306/pi.2014.11.4.380
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Risk Factors Associated with Internet Addiction in Korea

Abstract: ObjectiveThe aim of this study was to examine the prevalence of Internet addiction in middle school students and to identify associated psychosocial risk factors and depression.MethodsThis study was part of a larger epidemiological study on childhood psychiatric disorders conducted in Osan, a city of Republic of Korea. We used IAS for internet addiction, K-YSR for subjects' emotional and behavioral problems and K-CDI for depressive symptoms. We used the data of n=1217 completed cases. We put on independent var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
41
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 23 publications
(35 reference statements)
6
41
0
1
Order By: Relevance
“…27,29 In a Korean study, the correlation between internet addiction and depression was 67% that showed the highest percentage of co-morbidity with internet addiction among all psychological disorders. 32 It was also consistent with the reports from an Indian study. 33 Odds ratio (OR) in a Turkish study between internet addiction and depression was estimated to be 1.180.…”
supporting
confidence: 90%
“…27,29 In a Korean study, the correlation between internet addiction and depression was 67% that showed the highest percentage of co-morbidity with internet addiction among all psychological disorders. 32 It was also consistent with the reports from an Indian study. 33 Odds ratio (OR) in a Turkish study between internet addiction and depression was estimated to be 1.180.…”
supporting
confidence: 90%
“…Also consistent with previous studies, the total difficulties score on the SDQ‐P was significantly associated with PIU (Ozturk, Ekinci, Ozturk, & Canan, ). Other studies from Korea have also shown that behavioral problems, such as conduct problems, hyperactivity, and inattention, are associated with PIU (Lee et al, ). Behavioral problems in adolescents may negatively impact peer and family relationships and increase difficulties during daily functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Although PIU may be a strategy for coping with stress (Chou et al, 2015), the present results suggest that adolescents who experience academic stress and lack other leisure-time activities may use the Internet as an unhealthy coping mechanism. According to the limited number of studies conducted in Korea and abroad, early exposure to the Internet has been significantly associated with PIU (Lee, Shin, Cho, & Shin, 2014;Ni, Yan, Chen, & Liu, 2009). Our results support these findings.…”
Section: Discussionmentioning
confidence: 99%
“…University students are especially vulnerable to developing dependence on the Internet, more than most other segments of the society. This can be attributed to several factors including the following: Availability of time; ease of use; unlimited access to the Internet; the psychological and developmental characteristics of young adulthood; limited or no parental supervision; some courses are Internet-dependent, from assignments and projects to communication with peers and mentors; the Internet offering a route of escape from examination stress, all of which make Internet overuse a significant cause of concern for parents and faculty (Lee et al, 2014). This health concerns necessitate urgent awareness, prevention and prompt intervention to curb the menace.…”
Section: Introductionmentioning
confidence: 99%